To the problem of linguistic affiliation of the bearers of multirolled ceramic culture - Konstantin Alexandrovich Alekseev (Вестник Майкопского государственного технологического университета, 2023)
At this stage of archaeological and anthropological research, a consensus of opinions has developed regarding the course of the historical process in the Black Sea steppes in the Bronze Age. Thanks to this, it has become possible not only to determine the origin and genetic relationships of individual archaeological cultures, but also to resolve the problem of the ethnolinguistic affiliation of the bearers of these cultures. The purpose of the research is a comprehensive analysis of the available data of linguistics, glottochronology, mythology, archeology, anthropology and paleogenetics in order to formulate a hypothesis of linguistic attribution of the culture of multi-rolled ceramics. After determining the linguistic affiliation of the carriers of the culture of multi-rolled ceramics, a private task was to trace the historical fate of the identified dialects until the release of their carriers to modern habitats.The main method chosen was a retrospective deepening from the culture of multi-rolled ceramics to its origins and alleged ancestors. From the point of view of archeology and anthropology, the ancestors of the carriers of the culture of multi-rolled ceramics turn out to be the Zhivatilovo-Volchanskaya filiation of the Trypillian culture. Together with the inhabitants of Mikhailovka II, they have a genetic connection with the urban-Kasperovkaya group of the Trypillian culture. Since the Yamniks of Mikhailovka II are more or less reliably attributed as Satem Indo-Iranians, we have come the key conclusion, defining the own place of the carriers of the culture of multi-rolled ceramics in the system of areal-dialect divergence of the Indo-European language family, that they themselves and their Zhivtilovo-Volchan ancestors spoke archaic the Kafir dialects, characterized by the absence of palatalization of the phonetic series.